MATHEMATIC FINGER GAME BERPENDEKATAN OPEN-ENDED DALAM OPERASI HITUNG PENJUMLAHAN PADA SISWA SEKOLAH DASAR - Mursidik, Elly's Mersina; Ambarwati, Veni (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
The research objective is to provide alternative solutions in helping elementary school students to improve the basic calculation operations of addition through interactive learning using mathematic finger game. The research subjects were low grade elementary school students (grades 1, 2 and 3). This development research uses the Dick and Carey method with the stages of identifying goals, analyzing needs, identifying students' initial behavior, formulating goals, developing criteria reference tests, developing learning strategies, developing and selecting learning media, designing. Mathematic finger game is a combination of three finger games, namely Hompipah, Indonesian suit and Japanese suit which are used in determining the winner. The combination of these games is associated with the basic calculation operation of addition. The games are packaged into interactive learning with an open-ended approach by involving the ability to think creatively in answering problems according to directed thinking freedom and the ability to think critically in giving and receiving input on answers to problem solving that can be logically accepted.